Rancang Bangun Sistem Pakar dalam Menentukan Resiko Penyakit Jantung Koroner - Susangto Andi Putera S.; Silvia Rostianingsih; Kartika Gunadi (Jurnal Infra, 2020)
Currently, the use of expert system applications has been widely used by many people, and is supported by a very significant development. So it's easy to use by many people and has many benefits to support life today. With this application, ordinary people can easily learn the expertise of an expert so that it can be applied in everyday life. In this application, an expert system is applied to analyze the risk of a person to develop coronary heart disease and be able to do prevention as early as possible. In making this application, the programmer consulted experts (doctors) in making knowledge base (basis pengetahuan). Based on data test results, the application can work well and easily in its use. Application can provide good analysis results in diagnosing the possibility of cardiovascular disease using the parameters provided.Currently, the use of expert system applications has been widely used by many people, and is supported by a very significant development. So it's easy to use by many people and has many benefits to support life today. With this application, ordinary people can easily learn the expertise of an expert so that it can be applied in everyday life. In this application, an expert system is applied to analyze the risk of a person to develop coronary heart disease and be able to do prevention as early as possible. In making this application, the programmer consulted experts (doctors) in making knowledge base (basis pengetahuan). Based on data test results, the application can work well and easily in its use. Application can provide good analysis results in diagnosing the possibility of cardiovascular disease using the parameters provided.